Remembering Armenian music in Bolis: Komitas Vardapet in transcultural perspective. (October 2019) - Olley, Jacob
This article explores the relationship between music, memory and transcultural processes in late Ottoman Istanbul by studying the writings of the Armenian composer and musicologist Komitas Vardapet (1869–1935). It describes the changing political and intellectual landscape in which Komitas and his contemporaries redefined the collective musical memory of the Armenian people through a process of secularisation and internationalisation. I argue that there was a shift from local transculturalism, in which musical memories were to some extent shared between different ethnic and confessional groups in the Ottoman Empire, to a more global and modern transculturalism, in which consciously differentiated and often antagonistic national musical memories were constructed and disseminated across non-local spaces through new media and discursive strategies. In the process, rural music practices were appropriated from their local and unofficial contexts by urban, cosmopolitan elites and purposefully inscribed as monuments of Armenian cultural memory which have endured to the present.